2021
DOI: 10.3390/nano11061502
|View full text |Cite|
|
Sign up to set email alerts
|

Genotoxicity and Gene Expression in the Rat Lung Tissue following Instillation and Inhalation of Different Variants of Amorphous Silica Nanomaterials (aSiO2 NM)

Abstract: Several reports on amorphous silica nanomaterial (aSiO2 NM) toxicity have been questioning their safety. Herein, we investigated the in vivo pulmonary toxicity of four variants of aSiO2 NM: SiO2_15_Unmod, SiO2_15_Amino, SiO2_7 and SiO2_40. We focused on alterations in lung DNA and protein integrity, and gene expression following single intratracheal instillation in rats. Additionally, a short-term inhalation study (STIS) was carried out for SiO2_7, using TiO2_NM105 as a benchmark NM. In the instillation study,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Some in vivo and in vitro studies have shown that SiO 2 NPs can cause toxicity to different organs in the human body; toxicity has been demonstrated in lung epithelial cells [ 9 ], liver cells [ 10 ], intestinal cells [ 11 ], the lungs [ 12 ], and kidneys [ 13 ]. In addition, SiO 2 NPs were found to induce genotoxicity and alterations in gene and protein expression [ 12 , 14 ], and Chen et al [ 15 ] reported that SiO 2 NPs can induce cornea toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some in vivo and in vitro studies have shown that SiO 2 NPs can cause toxicity to different organs in the human body; toxicity has been demonstrated in lung epithelial cells [ 9 ], liver cells [ 10 ], intestinal cells [ 11 ], the lungs [ 12 ], and kidneys [ 13 ]. In addition, SiO 2 NPs were found to induce genotoxicity and alterations in gene and protein expression [ 12 , 14 ], and Chen et al [ 15 ] reported that SiO 2 NPs can induce cornea toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Some in vivo and in vitro studies have shown that SiO 2 NPs can cause toxicity to different organs in the human body; toxicity has been demonstrated in lung epithelial cells [ 9 ], liver cells [ 10 ], intestinal cells [ 11 ], the lungs [ 12 ], and kidneys [ 13 ]. In addition, SiO 2 NPs were found to induce genotoxicity and alterations in gene and protein expression [ 12 , 14 ], and Chen et al [ 15 ] reported that SiO 2 NPs can induce cornea toxicity. The local ocular delivery of medicine has become an important strategy for treating retinal diseases [ 16 18 ], and intravitreal injection has become a common treatment method for various retinal diseases including diabetic retinopathy, macular degeneration, macular edema, and inflammatory diseases [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation